Maternal and fetal outcomes in gestational diabetes mellitus: a narrative review of dietary interventions - Anuja Phalle; Devaki Gokhale (Frontiers in Global Women's Health)
IntroductionGestational diabetes mellitus (GDM) is associated with a myriad of maternal and fetal complications that severely compromise the mother and child's future health. Dietary interventions are effective in reducing the risk of GDM. However, when diagnosed with GDM in 2nd and 3rd the effectiveness of these interventions on maternal and fetal health remains unexplored. Therefore, this review critically examines existing literature for short- and long-term maternal and fetal outcomes of dietary interventions followed after GDM diagnosis.MethodologyAn extensive literature search through Scopus, PubMed, and Web of Science was conducted to include original, full-text articles published in English between 2013 and April 2024. All randomized controlled trials, case-control, prospective cohort studies, and longitudinal follow-up trials that recruited GDM mothers following dietary interventions upon diagnosis were included. However, pre-pregnancy interventional, retrospective, and prospective studies reporting maternal and fetal outcomes in healthy pregnant women were excluded. This review followed the Narrative Review Checklist by the Academy of Nutrition & Dietetics, Elsevier.ResultsWe reviewed the effects of eight popular dietary interventions on various short and long-term materno-fetal outcomes in women recently diagnosed with GDM. Dietary interventions such as Mediterranean, Dietary Approaches to Stop Hypertension (DASH), and low-GI positively affected both short and long-term maternal and fetal outcomes. In contrast, fasting during Ramadan negatively affected maternal and fetal outcomes. Studies with low-carb, high-protein, and calorie restriction reported mixed findings for materno-fetal outcomes. Although certain dietary interventions have shown beneficial effects in the past literature, their findings were limited by small sample size, short intervention duration, and inconsistencies in the outcomes and population studied, compromising the quality of evidence. Further, we observed a scarcity of studies exploring the effect of dietary interventions followed during 2nd and 3rd trimesters after being diagnosed with GDM on long-term materno-fetal outcomes.ConclusionDietary interventions followed during 2nd and 3rd trimesters after the diagnosis of GDM may be crucial for preventing short and long-term materno-fetal complications; however, there is a lack of strong evidence to support this notion. Future studies are recommended to monitor the long-term materno-fetal outcomes of GDM.